Geología de la Cordillera Occidental y Altiplano al Oeste del Lago Titicaca Sur del Perú (Proyecto Integrado del Sur). Hojas: 31-t, 31-u, 31-v, 31-x, 31-y, 32-s, 32-t, 32-u, 32-v, 32-x, 32-y, 33-v, 33-x, 33-y, 33-z - [Boletín A 42] - Palacios Moncayo, Oscar (1993)
257 p.